PENGARUH NET EKSPOR, KURS YUAN, DAN NET FDI TIONGKOK TERHADAP PEREKONOMIAN INDONESIA - Martin Ningsih, Ni Putu Diah; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 8 (2022): VOL11NO 8, AGUSTUS 2022 [2900-3323]DO - 10.24843/EEP.2022.v11.i08.p01, 2022)
Indonesia is one of the developing countries in the world that is experiencing quite good economic growth. However, the Indonesian economy is not always in a stable condition, from 1997 to 2014 Indonesia has experienced two crises, namely the Asian financial crisis (1997-1999) and the global crisis (2007-2008) which was marked by the emergence of disturbances in macroeconomic indicators. The objectives of this study are (1) to analyze the effect of China's Net Exports, Yuan Exchange Rate, and Net FDI simultaneously on the Indonesian Economy and (2) to analyze the effect of China's Net Exports, Yuan Exchange Rate, and Net FDI partially on the Indonesian Economy. This study observes data over a period of nineteen years (2000 to 2018), the data observed is per semester, so that the total amount of data observed is 38 (thirty eight) data. The analysis technique used in this research is multiple linear regression. The results of this study are (1) Net exports, the yuan exchange rate, and China's net FDI simultaneously have a significant effect on the Indonesian economy and (2) partially Net exports do not have a positive and significant effect on the Indonesian economy while the Chinese yuan exchange rate and Net FDI have an effect. positive and significant impact on the Indonesian economy. Keywords : Indonesian Economy, Net Exports, Yuan Exchange Rate, China's Net FDI